(untitled) - Faerber, Esmé (New York, 2008)
Includes bibliographical references and index; Why invest in stocks -- Common stocks -- Preferred stocks -- Understanding the risks of investing in stocks -- Returns of stocks -- Stock market indexes -- How stocks are traded -- How short selling works -- Valuing common stock -- Financial statement analysis and fundamental analysis -- Technical analysis -- Theories of the stock market -- Growth, value, and momentum investing styles -- Open-end mutual funds -- Closed-end funds -- Exchange-traded funds -- Investing in foreign stocks -- Portfolio management and evaluation
Keywords: Finance -- Personal; Investments; Tài chính -- Cá nhân; Đầu tư